Structure-tailored non-noble metal-based ternary chalcogenide nanocrystals for pt-like electrocatalytic hydrogen production - Sarkar, Shreya; Rawat, Abhishek; Das, Tisita; Gaboardi, Mattia; Chakraborty, Sudip; Vinod, C. P.; Peter, Sebastian C. (ChemSusChem, 2021)
A facile microwave-assisted strategy was employed to synthesize Ni3Bi2S2 nanocrystals. Variation in the synthesis conditions tuned the composition of monoclinic and orthorhombic phases of Ni3Bi2S2. The electrochemical hydrogen evolution activity of the catalyst with highest percentage of monoclinic phase demonstrated a negligible onset potential of only 24 mV close to that of state-of-the-art Pt/C with an overpotential as low as 88 mV. Density functional theory calculations predicted the monoclinic phase exhibit the lowest adsorption free energy corresponding to hydrogen adsorption (Delta GadsH*) and, therefore, the highest hydrogen evolution activity amongst the considered phases. The quasi-2D structure of monoclinic phase facilitated an increased charge-transfer between Ni and Bi, favoring the downward shift of the d-band center to enhance the catalytic activity.
Keywords: charge transfer; electrocatalysis; hydrogen evolution reaction; Nanomaterials; ternary chalcogenides